Language Problems in Science Communication at a Multilingual Setting: A Review Study - Budhathoki, Naba Raj (Khwopa Journal, 2025)
Communicating scientific and technological discoveries to the public is seen as science communication as opposed to scientific communication. Technical language and style are extensively required for discussing scientific concepts and discoveries. In specialized disciplines, their use makes concepts more precise and clearer; however, it can present difficulties to communicate the scientific information to the public. This review examines the major components of scientific language, namely readability, sentence structure, and jargon usage. In addition to discussing methods for enhancing the readability and clarity of scientific literature, it looks into how these linguistic characteristics affect science communication, such as earthquake related communication. Additionally, the review highlights new research on how jargon and complex sentence structures coupled with frequent passive voice may affect the public’s comprehension and acceptance of scientific knowledge in a multilingual situation, demanding setting-specific studies.